Volatile-mediated suppression of plant pathogens is related to soil properties and microbial community composition - van Agtmaal, Maaike; Straathof, Angela L.; Termorshuizen, Aad; Lievens, Bart; Hoffland, Ellis; de Boer, Wietse (Soil biology & biochemistry, 2018)
There is increasing evidence that the soil microbial community produces a suite of volatile organic compounds that suppress plant pathogens. However, it remains unknown which soil properties and management practices influence volatile-mediated pathogen suppression. The aim of this study was to relate soil properties to growth suppression of three plant pathogens by soil volatiles. We measured the effect of volatiles emitted from a broad range of agricultural soils on the in vitro growth of the plant pathogenic fungi Rhizoctonia solani and Fusarium oxysporum, and the oomycete Pythium intermedium. Growth suppression of pathogens by soil volatiles could be linked to various soil properties, and some aspects of microbial community composition and field history, using multiple linear regression. Volatile-mediated suppression of mycelial development occurred for each pathogen type, but the magnitude of inhibition differed among soils as well as pathogens. On average R. solani and P. ultimum appeared more sensitive to volatile suppression than F. oxysporum. Suppression of R. solani by volatiles was positively correlated with organic matter content, microbial biomass and proportion of litter saprotrophs in the microbial community, but negatively correlated with pH, microbial diversity (Shannon), and the proportion of Acidobacteria in the community. R. solani, F. oxysporum, and P. intermedium suppression by volatiles was affected by various management practices occurring in the soil's field history, such as reduced tillage, the presence of certain crops in the crop rotation, and the application of solid manure. P. intermedium suppression was also negatively correlated with soil sulphur content. This study identifies pathogen-specific drivers of growth-suppressive volatiles, a critical step in integrating soil volatiles into prediction and management of soil-borne plant diseases. •Volatiles from 50 soils suppressed growth of three pathogens in 91% of pairings.•Rhizoctonia solani suppression was most related to soil organic matter content.•Fusarium oxysporum and Pythium intermedium suppression was driven by field management.•Microbial community attributes only explained a small proportion of suppression.•Results suggest natural suppression by volatiles can be promoted via management.